2009
DOI: 10.1261/rna.1869710
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of Aubergine mediates Tudor binding and germ plasm localization

Abstract: Piwi proteins such as Drosophila Aubergine (Aub) and mouse Miwi are essential for germline development and for primordial germ cell (PGC) specification. They bind piRNAs and contain symmetrically dimethylated arginines (sDMAs), catalyzed by dPRMT5. PGC specification in Drosophila requires maternal inheritance of cytoplasmic factors, including Aub, dPRMT5, and Tudor (Tud), that are concentrated in the germ plasm at the posterior end of the oocyte. Here we show that Miwi binds to Tdrd6 and Aub binds to Tudor, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 70 publications
4
157
0
Order By: Relevance
“…For example, components of germ granules, such as Piwi-family argonautes, harbor methylated arginines that help recruit tudor domain-containing proteins. Interfering with this interaction can impair both localization of tudor-domain proteins, and the methylated proteins themselves, 48,49 as well as germ granule assembly. 50 Such interactions also underpin recruitment of tudor-domain proteins to stress granules.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…For example, components of germ granules, such as Piwi-family argonautes, harbor methylated arginines that help recruit tudor domain-containing proteins. Interfering with this interaction can impair both localization of tudor-domain proteins, and the methylated proteins themselves, 48,49 as well as germ granule assembly. 50 Such interactions also underpin recruitment of tudor-domain proteins to stress granules.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…KPN), which we described previously (Kirino et al 2010), were immobilized on two flow cells of an avidin-coupled sensor chip (BioCap, SensiQ). For immobilization, 150 μL of a 10 μg/mL peptide solution in running buffer was injected onto the sensor surface at 470 or 430 response units (RUs).…”
Section: Rnai Knockdown Of Target Gene Expression In Bmn4 Cellsmentioning
confidence: 99%
“…It has been reported that the Drosophila dPRMT5 gene encodes a protein arginine methyltransferase (PRMT) that specifically catalyzes symmetric dimethylation of arginine residues of PIWI proteins (Kirino et al, 2009). Mass spectrometry analyses have revealed that PIWI, but not AGO, subfamily proteins are arginine methylated at their N termini Nishida et al, 2009;Vagin et al, 2009), which is important for the recognition of specific TUDOR family proteins Kirino et al, 2010;Nishida et al, 2009;Reuter et al, 2009;Shoji et al, 2009;Vagin et al, 2009;Wang et al, 2009). For example, TUDOR, one of the Drosophila TUDORdomain-containing proteins, associates with AUB and AGO3 in an sDMA-dependent manner (Kirino et al, 2010;Nishida et al, 2009).…”
Section: Papi Binds To Symmetrically Dimethylated Arginine Residues Imentioning
confidence: 99%
“…Mass spectrometry analyses have revealed that PIWI, but not AGO, subfamily proteins are arginine methylated at their N termini Nishida et al, 2009;Vagin et al, 2009), which is important for the recognition of specific TUDOR family proteins Kirino et al, 2010;Nishida et al, 2009;Reuter et al, 2009;Shoji et al, 2009;Vagin et al, 2009;Wang et al, 2009). For example, TUDOR, one of the Drosophila TUDORdomain-containing proteins, associates with AUB and AGO3 in an sDMA-dependent manner (Kirino et al, 2010;Nishida et al, 2009). The mouse TUDOR domain-containing proteins TDRD1, TDRD2 and TDRD9 also require the sDMA modification of the mouse PIWI proteins for their association Reuter et al, 2009;Shoji et al, 2009;Vagin et al, 2009;Wang et al, 2009).…”
Section: Papi Binds To Symmetrically Dimethylated Arginine Residues Imentioning
confidence: 99%
See 1 more Smart Citation